The Role of Parent Support and Confidence in the Learning Independence of High-Grade Elementary School Students - Vanny Noviana Indriani; Dwi Nastiti (Psikostudia : Jurnal Psikologi, 2024)
Learning independence is an attitude in individual learning to achieve goals and actively contribute to the learning process without relying on others. Students who have learning independence will be able to overcome various problems faced, especially in learning activities. However, the existing phenomenon shows that there are still students who have problems in learning independence, such as not evaluating their learning activities, giving up easily on difficult tasks, and not seeking information from various learning sources. The study aims to see the effect of parental support and self-confidence on learning independence at SDN Tanggul Sidoarjo. This research is correlational quantitative research. The study population consisted of high-grade students at SDN Tanggul Sidoarjo with a total of 124 students, and all students were used as research samples. The data collection technique in this study uses a scale of Parental Support, Self-Confidence, and Learning Independence. This technique is used to find out the effect of parental support and self-confidence on the learning independence of high school students. Analysis of the research results using multiple linear regression with the help of JASP. The results of the study showed a p value of 0.001 <0.05, which indicates a significant effect of parents' support and self-confidence on learning independence in high school students at SDN Tanggul Sidoarjo.Kemandirian belajar adalah sikaip dalam pembelaijaran individu untiuk mencapaii tujuan serta berkontriibusi aktif dalam proises pembelajaran tanpa bergiantung pada orang lain. Siswa yang memiliki kemandirian belajar akan mampu mengatasi berbagai masalah yang dihadapi, terutama dalam kegiatan pembelajaran. Namun, fenomena yang ada menunjuikkan baihwa masiiih terdiapat siiswa yang memiiliki masalah dalam kemandiirian beilajar, seperti tidak mengevaluasi kegiatan belajarnya, mudah menyerah pada tugas yang sulit, dan kurang mencari informasi dari berbagai sumber belajar. Penelitian bertujuan untuk melihat pengaruh dukungan orang tua dan kepercayaan diri terhadap kemandirian belajar di SDN Tanggul Sidoarjo. Penelitian ini merupakan penelitian kuantitatif korelasional. Populasi penelitian terdiri dari siswa kelas tinggi di SDN Tanggul Sidoarjo dengan jumlah 124 siswa, dan seluruh siswa dijadikan sampel penelitian. Teknik peingumpulan data dalam peneliitian ini menggiunakan skala Dukungan Orang Tua, Kepercayaan Diri, dan Kemandirian Belajar. Teknik ini diigunaikan uintiuk mengietahui peingiaruh dukungan oiraiing tuia dan kepercaiyaan diiri teirhadap kemaindirian beilajar paida sisiwa keilas tinggi sekolah dasar. Analisis hasil penelitian menggunakan regresi linear berganda dengan bantuan JASP. Hasil penelitian diketahui nilai p sebesar 0,001 < 0,05, yang mengindikasikan adanya pengaruh signifikan dukungan oraing tuia dan kepericayaan diri teirhadap keimandirian beilajar pada siiswa keilas tinggi di SDN Tanggul Sidoarjo.